Kepemimipinan Millenial Dalam Perpustakaan:Peluang dan Tantangan Dalam Menghadapi Era Revolusi Industri 4.0 - Abdul Rahman Simatupang (Central Library of Universitas Sebelas Maret, 2020)
Millennial leadership is a leadership that has a good innovation, high creativity, also sensitive to technology development and able to increasing employers motivation. Opportunities and challenges in the revolution era 4.0 are make information technology as promotional opportunity, and make information technology as a tools to exchanging ideas to advance the organization or institution being led, while the challenges that occur are the initial challenge of the leader himself, the socialization of design that is innovative, and always to upgrade and accept change as a form of challenges faced by leaders.